Empathy in Mental Health Nursing Care in Brazil - Fernandes Gambarelli, Samyra; Carelli Taets, Christian Marx; De Cunto Carelli Taets , Gunnar Glauco (Journal Of Nursing Practice, 2020)
Background: Empathy, from the Greek empathetic means to enter into the feeling, a term initially used by aesthetic theorists, to designate the ability to perceive the subjective experience of the other. For empathy to occur as a therapeutic process, it is essential that a relationship of mutual respect be developed and that nurses provide individualized care, respecting the culture, beliefs and values of the person. Purpose: This study aimed to determine to know and characterize the scientific production on Empathy in Mental Health Nursing Care in Brazil.Methods: This is a metasynthesis performed in the first half of 2018 that involved five stages: formulation of the problem, data collection, evaluation of the collected data, analysis and interpretation of the data, and presentation of the results.Results: Of the 6 studies that were part of this metasynthesis, the method most used among the forms of treatment among the health professional/patient is the biomedical model, focusing on the disease and not on the human being in a broad and holistic way, consequently, being performed only one punctual care and not a care in order to meet all the biopsychosocial needs of the patient.Â Conclusion: As a way to improve care and meet the patient's needs, empathy is one of the main tools of mental health care in Brazil, because with it we can gain trust and establish bonds with the patient, thus gaining an effective relationship for both parties, thus being able to perform an affectionate, integrative and productive care